A Pragmaic Analysis of Plasschaert's 'Briefings on Iraq - Prof. Enas Naji Kadim (PhD); Sarah Mohammed Jassim (Journal of College of Education, 2026)
The research examines the pragmaic elements in diplomatic discourse by analyzing two UN Security Council briefings delivered by SRSG Jeanine Hennis-Plasschaert about Iraq in 2024. The extensive study of diplomatic discourse has not addressed how pragmaic strategies operate in UN briefings about sensitive geopolitical situations specifically concerning Iraq. This study investigates diplomatic language operations throughout pragmatic which enables diplomats to fulfill their defined objectives while upholding international relations standards. The research employs Searle's (1969) Speech Act Theory and Grice's (1975) Theory of Implicature to analyze two February 6 and May 16, 2024 UN briefings through a qualitative methodology. The analysis shows how skilled representatives and directives work with conventional and conversational implicature to handle delicate matters without open confrontation. The research shows how UN briefings employ diplomatic discourse to handle multiple audiences while upholding institutional standards which enhances the knowledge of advanced linguistic methods in diplomatic communication at high levels
Keywords: Diplomatic discourse; Pragma-rhetorical analysis; UN briefings